Guidelines for intervention in streams, as border landscape structurers in Medellín, Colombia (REVISTA NODO, 2021)
The present work highlights the necessary inclusion of the landscape approach in the territorial ordering, particularly in wild-ruralurban borders, paying balanced attention to the categories that determine this approach: natural, built and human. The aim is to consolidate the streams as structurers of the border landscape on the slopes of the Aburrá valley, on which the city of Medellín extends. By taking advantage of the privileged geography, the natural wealth, the abundance of water and the significant landscape that the valley enjoys, it avoids progressive loss. The main result of this work is an approach to intervention guidelines in streams, particularly in its sections coinciding with the edge; these are directed to public administrators, designers and promoters involved in projects to be developed in this conjuncture area or ecotone, and therefore fragile landscape, specifically when it involves water currents. The proposal is to facilitate the conversion of landscape ideals into reality, to translate them from ambiguous thoughts to real facts in the territorial organization and appropriation of the daily space and the identity of the local landscape. As a first local attempt, it constitutes an invitation to expand the urgent and applied research, in the near future, on this relevant topic.
Keywords: Border landscape; Landscape approach; Hillside streams